Recovery of carbon and cryolite from spent carbon anode slag of electrolytic aluminum by flotation based on the evaluation of selectivity index - Wang, Yemin; Wang, Xuexia; Bilal, Muhammad (Frontiers in Chemistry, 2022)
One of the main electrolytic aluminum production costs is the consumption of carbon anodes, and carbon anode slag is a common hazardous waste in the aluminum industry. In this work, electrolytic aluminum carbon anode slag was separated by flotation. Using the selectivity index (SI) as an indicator, the influencing factors of the carbon slag flotation process were optimized, and the separation performance of carbon and cryolite in the carbon anode slag was investigated. The raw carbon anode slag was ground for 40 min to achieve dissociation of the cryolite from the carbon, the optimized SI value was then used to determine the optimal flotation test conditions. The test results showed that the SI value under the optimal grinding flotation was approximately four times larger than the value of direct flotation. This indicated that carbon anode slag had a better flotation selectivity under the grinding flotation, which significantly improved the flotation performance.